Ore-Forming Fluids of Orogenic Gold Deposit In Tamilouw-Haya, Seram Island, Indonesia - Herfien Samalehu; Arifudin Idrus; Nugroho Setiawan (Geological Agency, 2023)
The Tamilouw-Haya orogenic gold deposit is located in the southern arm of Seram Island, Indonesia, occupying Tehoru Metamorphic Complex. Gold mineralization is predominantly in the form of veins, stockwork, and breccia, although minor dissemination is slightly appeared in the rock float samples. Ore-mineral assemblages are dominated by native gold, pyrite, chalcopyrite, sphalerite, tetrahedrite-tennantite (sulfosalt), galena, pyrrhotite, marcasite, realgar, kalininite, and arsenopyrite. Covellite, hematite, goethite, and malachite appear as supergene minerals. High-grade gold ores in this area are generally found in quartz-carbonate veins with the main alteration processes involving silicification, carbonatization, and sericitic. The P-T history of the mineralization was revealed by fluid inclusions, and this study implies the depth of ore deposit and its evolution during mineralization. The primary fluid inclusions from three different types of quartz/quartz-carbonate veins in Tamilouw-Haya crystallized at the homogenization temperature (Th) of 240 °C to 340 °C, with a fluid salinity from 3.87 to 0.70 wt. % NaCl equivalent, and melting temperature (Tm) of -0.4 to -2.3 oC. The ore-forming fluids consist mainly of two-phase (VCO2+LH2O) liquid-rich aqueous inclusions, characterized by low to rich CO2, low salinity, and moderate temperature. There are three vein types as the ore-bearing fluids with precious metals and anomalous high basemetal contents. Quartz type 1- veins (V1); concordant veins, formed at a temperature of 240-307 oC with an average salinity of 1.8 wt. % NaCl equivalent. Quartz type 2- veins (V2) tend to cut the rock foliation which are formed at temperature range from 293-336 oC with the average salinity that shows a value of 2.4 wt. % NaCl equivalent. Meanwhile, type 3 quartz-carbonate veins (V3) are formed at the temperature range of 240-340 oC and the average salinity of 2.72 wt. % NaCl equivalent. These quartz-carbonate veins cut the wall-rock foliation, which is identified as the late stage and associated with ore deposition in Tamilouw-Haya. The gold deposit in Tamilouw-Haya is formed at a depth of about 5.5-9 km of paleosurface, and the pressure between 1.7-2.4 Kbar in epizonal to mesozonal zones. Keywords: Tamilouw-Haya, orogenic gold, fluid inclusion, microthermometry, ore-forming fluids